Strategi Manajemen Pembiayaan Pendidikan Dalam Meningkatkan Mutu Lulusan - Najwa Safira; Anik Rismaida; Wahyu Tri Setyobudi; Nur Intan Rochmawati; Sisca Septiani (Prodi PGSD Unsultra, 2026)
This study employed a qualitative approach and was conducted at SMP Negeri Unggul Tunas Nusa. The findings show that educational financing management was implemented through three main stages: planning, implementation, and evaluation. In the planning stage, the school prepared an annual budget based on operational needs, including facilities and infrastructure, teachers’ honoraria, learning activities, and educational quality improvement programs. The budgeting process was carried out participatively by involving the principal, the treasurer, and the school committee. In the implementation stage, funds were utilized in accordance with the approved budget plan while maintaining transparency and accountability, particularly in managing BOS funds and community contributions. In the evaluation stage, the school conducted periodic reviews of budget realization and spending effectiveness. This evaluation was conducted by the school management team in collaboration with the committee to ensure that educational financing contributed to improving educational quality and graduate quality. Overall, the implementation of educational financing management at SMP Negeri Unggul Tunas Nusa supported a more effective and efficient educational process. A well-structured and closely monitored financial management system became a key factor in promoting better educational outcomes and graduate quality at the school.